Inovasi Pembuatan Plafon Ramah Lingkungan dengan Substitusi Serat Daun Nanas dan Serbuk Daun Tembakau - Olivia Desriyatna Az-zahra; Laras Rafita Siwi; Hartono H; Riza Susanti (Jurnal Sipil dan Arsitektur, 2023)
Ceiling with a mixture of pineapple leaf fibers and tobacco powder as a substitute for gypsum flour is a new innovation that has physical and mechanical properties of ceilings that are better than conventional ceilings. The materials used in making this ceiling are gypsum flour, pineapple leaf fiber, tobacco leaf powder, epoxy resin, and distilled water. The types of tests carried out on this gypsum ceiling are flexural strength tests, density tests, thickness swelling tests, and water absorption tests. To compare between conventional ceilings and ceilings with added materials such as pineapple leaf fiber and tobacco leaf powder. The test was carried out after the gypsum ceiling reached the age of 7 days which was placed at room temperature. The flexural strength test was carried out with 5 specimens, while the thickness swelling test and water absorption test were carried out with 2 specimens. In the manufacture of this test object, there are as many as 3 variations, where variation A is a conventional ceiling which means 0% mixture. Then variation B with a mixture of 2% for pineapple leaf fiber and 1% for shot leaf powder. Furthermore, the last variation is variation C with a mixture of 5% pineapple leaf fiber and 1% tobacco leaf powder. The result of the test is that the optimal test object is produced with characteristics according to SNI 01-4449-2006, namely in variation B where variation B has a flexural strength value of 71.66% better than conventional ceilings, 0.79% better in density testing compared to conventional ceilings, and 4.7% better than the water absorption value of conventional ceilings.